COMPUTER SIMULATION OF THE COMBINED USE OF AZATHIOPRINE WITH METHYLPREDNISOLONE UNDER THE CONDITIONS OF PHARMACOTHERAPY OF MYASTHENIA GRAVIS - Larionov, V.B.; Nefodov, O.O.; Kalbus, O.I.; Titov, G.I.; Nefodova, O.O.; Onul, N.M.; Rutgaizer, V.G. (World of Medicine and Biology, 2022)
The combined use of physiologically active compounds is aimed at optimizing their combined pharmacotherapeutic effect, which provides for reducing adverse reactions of ingredients, reducing their doses under conditions of potential synergism of the used components and increasing the convenience of taking ready-made medicinal forms. The purpose of this study was to assess the possibility of combined use, effectiveness and safety of azathioprine and methylprednisolone in the treatment of myasthenia gravis. Possible chemical reactions of the compounds were predicted based on the presence and reactivity of the functional groups included in their structure. The analysis of the acid-base properties of the compounds was carried out using the ACD/pKaDB and ChemAxon programs. Analysis of physicochemical properties and data on the interaction with enzyme systems for methylprednisolone and azathioprine suggests the absence of possible interactions between these drugs at the chemical and pharmacokinetic levels (with the need to adjust dosage regimens). At the pharmacological level, the combined therapeutic effect of methylprednisolone and azathioprine is expected to contribute to more effective treatment of multiple sclerosis by inhibiting the development and course of inflammatory reactions.